High-strength biodegradable zinc alloy implants with antibacterial and osteogenic properties for the treatment of MRSA-induced rat osteomyelitis. (August 2022) - Jia, Bo; Zhang, Zechuan; Zhuang, Yifu; Yang, Hongtao; Han, Yu; Wu, Qiang; Jia, Xiufeng; Yin, Yanhui; Qu, Xinhua; Zheng, Yufeng; Dai, Kerong
Abstract: Implant-related infections caused by drug-resistant bacteria remain a major challenge faced by orthopedic surgeons. Furthermore, ideal prevention and treatment methods are lacking in clinical practice. Here, based on the antibacterial and osteogenic properties of Zn alloys, Ag and Li were selected as alloying elements to prepare biodegradable Zn-Li-Ag ternary alloys. Li and Ag addition improved the mechanical properties of Zn-Li-Ag alloys. The Zn-0.8Li-0.5Ag alloy exhibited the highest ultimate tensile strength (>530 MPa). Zn-Li-Ag alloys showed strong bactericidal effects on methicillin-resistant Staphylococcus aureus (MRSA) in vitro . RNA sequencing revealed two MRSA-killing mechanisms exhibited by the Zn-0.8Li-0.5Ag alloy: cellular metabolism disturbance and induction of reactive oxygen species production. To verify that the therapeutic potential of the Zn-0.8Li-0.5Ag alloy is greater than that of Ti intramedullary nails, X-ray, micro-computed tomography, microbiological, and histological analyses were conducted in a rat femoral model of MRSA-induced osteomyelitis. Treatment with Zn-0.8Li-0.5Ag alloy implants resulted in remarkable infection control and favorable bone retention. The in vivo safety of this ternary alloy was confirmed by evaluating vital organ functions and pathological morphologies. We suggest that, with its good antibacterial and osteogenic properties, Zn-0.8Li-0.5Ag alloy can serve as an orthopedic implant material to prevent and treat orthopedic implant-related infections.